Dimetia brevipetiolata (Spermacoceae: Rubiaceae): A new species from Guangxi, China - Zhang, Ying; Jiang, Guo-Bin; Wang, Rui-Jiang (Phytotaxa, 2020)
A new species, Dimetia brevipetiolata R. J. Wang, from Guangxi Zhuang Autonomous Region, China, is described and photographed. Morphologically, it is similar to D. scandens and D. ampliflora with respect to their terete stem, lanceolate and thick papery leaves and compound-cymose inflorescences, but differs in prostrate habit, subsessile leaves, rounded leaf base, nearly glabrous corolla, and indehiscent capsules. The molecular phylogenetic analysis revealed that D. brevipetiolata was embedded in the Dimetia clade and closely related to D. auricularia. It is evaluated as Least Concern according to IUCN Red List Categories and Criteria.